Bioactive Glasses Potential Biomaterials for Future Therapy - Kaur, Gurbinder; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book describes the history, origin and basic characteristics of bioactive materials. It includes a chapter dedicated to hydroxyapatite mineral, its formation and its bioactive properties. The authors address how cytotoxicity is a determining step for bioactivity. Applications of bioactive materials in the contexts of tissue regeneration, bone regeneration and cancer therapy are also covered. Silicate, metallic and mesoporous glasses are described, as well as the challenges and future prospects of research in this field.
Understanding Bioactive Materials -- Bioactivity in terms of hydroxyapatite -- Cytocompatibilty and pH balance -- Categories of bioactive materials -- Silicate, borate and borosilicate glasses -- Metallic glasses and coatings -- Mesoporous glasses -- Targeted Drug delivery -- Future and fate of bioactive materials.
Keywords: Biomedical engineering; Ceramic materials; Coatings; Tribology; Corrosion and anti-corrosives.; Biomedical Engineering and Bioengineering; Ceramics; Coatings; Tribology; Corrosion